108k views
1 vote
simplify the expression write your answer as a complex number. three square root of 16 plus square root of - 9​

User Vladimyr
by
4.9k points

1 Answer

5 votes

Answer:


\large\boxed{3√(16)+√(-9)=12+3i}

Explanation:


3√(16)+√(-9)\\\\√(16)=4\ \text{because}\ 4^2=16\\\\√(-9)=√((9)(-1))\qquad\text{use}\ √(ab)=√(a)\cdot√(b)\\=\sqrt9\cdot√(-1)=(**)\\\sqrt9=3\ \text{because}\ 3^2=9\\√(-1)=i\\(**)=3i\\\\3√(16)+√(-9)=(3)(4)+3i=12+3i

User Morteza Asadi
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.